2021
DOI: 10.1109/access.2021.3107426
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Effect of Data Breach Publicity on Information Security Awareness Using Hierarchical Regression

Abstract: The technological evolution has formed new challenges for organizations to safeguard their information as digital assets. Information Security Awareness (ISA) is the cognitive state where individuals possess the comprehension of information security, threats, and the capability to develop preventive strategies. Prior studies discovered that human mistakes or misbehavior is the most vulnerable link in information security due to insufficient security awareness. There were massive data breaches reported througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Hwang et al (2019) investigated how ISA leads to improved information security compliance behavior and found that it is crucial to invigorate awareness before any behavioral changes could happen. Siponen (2000) and Khan et al (2011) also supported that awareness is the first step to information security behavioral change, which would require more than providing information about security risks via campaigns (Bada et al , 2019) because individuals are driven by different knowledge through factors such as experience (Jaeger and Eckhardt, 2021), security warnings (Jaeger and Eckhardt, 2021) and data breach publicity (Chua et al , 2021b). Since individual knowledge influences attitude and intention to change security-related behavior (Bada et al , 2019; Chin and Chua, 2021; Jaeger and Eckhardt, 2021), it is crucial to have conceptual and procedural understanding of ISA (Khan et al , 2011; Siponen, 2000).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Hwang et al (2019) investigated how ISA leads to improved information security compliance behavior and found that it is crucial to invigorate awareness before any behavioral changes could happen. Siponen (2000) and Khan et al (2011) also supported that awareness is the first step to information security behavioral change, which would require more than providing information about security risks via campaigns (Bada et al , 2019) because individuals are driven by different knowledge through factors such as experience (Jaeger and Eckhardt, 2021), security warnings (Jaeger and Eckhardt, 2021) and data breach publicity (Chua et al , 2021b). Since individual knowledge influences attitude and intention to change security-related behavior (Bada et al , 2019; Chin and Chua, 2021; Jaeger and Eckhardt, 2021), it is crucial to have conceptual and procedural understanding of ISA (Khan et al , 2011; Siponen, 2000).…”
Section: Introductionmentioning
confidence: 87%
“…Moody et al (2018) urged that ISA, through educational campaigns or training, should include knowledge related to information technology security threats, their consequences and the protective actions to remove them. Furthermore, Chua et al (2021b) found that individuals who received more data breach news (that may invoke fear) will have higher ISA. Therefore, we hypothesize that fear will affect one's ISA: H5.…”
Section: Emotion Toward Knowledgementioning
confidence: 99%
“…In addition, the massive impact of data breaches involves internal and external consequences for the organization [4]. Internal consequences affect the breached organization in terms of operations [5], [6], workforce [7]- [9], legal issues [10], [11], and finance [12], [13]; external consequences affect customers [14]- [16], competitors [17], [18], suppliers [19]- [21], and other stakeholders [22]. As an example of financial impacts, according to a report by IBM, global losses from data breach incidents increased from USD 3.86 billion in 2020 to USD 4.24 billion in 2021 [23] and USD 4.35 billion in 2022 [24].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cloud computing has been widely used in many areas of everyday life, mainly for data storage [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cloud computing has been widely used in many areas of everyday life, mainly for data storage [ 1 , 2 ]. This raises questions about the reliability and how to manage the data in question.…”
Section: Introductionmentioning
confidence: 99%